Upaya Masyarakat dalam Mengatasi Dekadensi Moral Remaja di Gampong Beunot, Syamtalira Bayu, Aceh Utara - Miftahul Jannah (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2021)
Adolescence is a phase of life experienced by every individual from childhood to adulthood, at this time adolescents are very vulnerable to negative influences, such as theft, drug use, and other things that trigger deviant behavior. The surrounding environment greatly influences the formation of a teenager's character, because teenagers generally spend more of their time in association with their friends or with the surrounding community. Gampong Beunot is the most densely populated village in Syamtalira Bayu District, its heterogeneous population makes the Gampong Beunot community more open. Even though society is more open, social phenomena are also unavoidable, especially with regard to teenagers, from 2010 to 2017 Gampong Beunot is the Gampong with the most frequent occurrence of moral decadence, this causes public unrest and discomfort then the condition changes to a more better over time compared to the past. This is undeniable because the community has made various efforts and efforts, from the preventive, persuasive to the repressive stages which of course will face various obstacles. This type of research is a qualitative research that uses field research methods using primary and secondary data. The data collection techniques used are observation, interviews and documentation. The findings of this study indicate that the preventive measures taken by the Gampong Beunot community in overcoming the moral decadence of adolescents are by holding regular recitations, counseling, sports programs, women's programs, and curfew rules, while Persuasive steps taken by the Gampong Beunot community are persuasive communication and exclamation banners, and also for repressive actions carried out by the Gampong Beunot community, namely by giving customary sanctions, criminal penalties, besides that the Gampong Beunot community also has several obstacles in overcoming the moral decadence of teenagers namely the apathy of society, uncooperative parents of teenagers, and teenagers who have a brutal and aggressive nature.